2003
DOI: 10.1038/nmat900
|View full text |Cite
|
Sign up to set email alerts
|

Pinpoint and bulk electrochemical reduction of insulating silicon dioxide to silicon

Abstract: Silicon dioxide (SiO(2)) is conventionally reduced to silicon by carbothermal reduction, in which the oxygen is removed by a heterogeneous-homogeneous reaction sequence at approximately 1,700 degrees C. Here we report pinpoint and bulk electrochemical methods for removing oxygen from solid SiO(2) in a molten CaCl(2) electrolyte at 850 degrees C. This approach involves a 'contacting electrode', in which a metal wire supplies electrons to a selected region of the insulating SiO(2). Bulk reduction of SiO(2) is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
401
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 403 publications
(421 citation statements)
references
References 12 publications
18
401
1
1
Order By: Relevance
“…Therefore, the negative electrochemical potential should be supplied to TiO 2 , i.e., TiO 2 should contact with the cathode electrically and accept the electron from the cathode. Okabe et al [22][23][24] and Nohira et al 25) pointed the importance of electron transfer from the cathode to TiO 2 .…”
Section: Reduction Of Tio 2 By Electrolyzed Camentioning
confidence: 99%
“…Therefore, the negative electrochemical potential should be supplied to TiO 2 , i.e., TiO 2 should contact with the cathode electrically and accept the electron from the cathode. Okabe et al [22][23][24] and Nohira et al 25) pointed the importance of electron transfer from the cathode to TiO 2 .…”
Section: Reduction Of Tio 2 By Electrolyzed Camentioning
confidence: 99%
“…16,17 In this synthesis, it is found that the electrode structure plays an important role in the growth of Si NWAs. The nickel nets in the sandwich structure of the electrode (Fig.…”
mentioning
confidence: 99%
“…Nohira et al (14) reported that CaSi/CaSi 2 and pure Si were obtained above 2.8 V and below 2.45 V, respectively, when the SiO 2 plate was reduced. This indicates the contribution of Ca in the formation of Ca-based alloys, but a less active Ca does not form these alloys although it can reduce SiO 2 .…”
Section: Ffc Processmentioning
confidence: 99%